Continuous professional development: Perceptions of secondary school teachers in Zambia - Muyunda, Gift (Electronic Journal of Education, Social Economics and Technology, 2022)
Teacher professional development (TPD) is not only an ongoing process that contributes towards individual growth of teachers but also an integral element in school improvement. This paper reports the Zambian secondary school teachers’ perceptions of their continuous professional development in teacher engagement in CPD activities, perceived importance of different CPD programs/activities, needs to be focused on future training, and barriers using quantitative data. A self-created questionnaire was distributed to 700 conveniently selected secondary school teachers from four schools. The data was examined using descriptive statistics such as frequency of responses, mean scores, and standard deviation, as well as the t-test of independent samples for comparing the perspectives of respondents from different categories. From the findings, teachers were moderately engaged in TPD programs/activities and perceived developing teaching and learning materials as highly important. The impact of their perceptions was evident as there was no significant difference between female and male perceptions about their engagement in teacher CPD programs. Thus, the importance of recognizing and addressing teachers' perceptions of CPD is argued in this study because teachers play an important role in how they learn and how their perceptions impact the changes they make in their teaching practice.